SYNTHESIS OF MANIPULATION ROBOT PROGRAM TRAJECTORIES WITH CONSTRAINTS IN THE FORM OF OBSTACLES - Baybatshaev, Muhit; Beysembaev, Akambay (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The paper presents a method of synthesis of manipulation robot motion trajectory according to mobility degrees. The configuration of the manipulator parts and obstacles are approximated by semiinfinite spaces limited by planes. The fact of robot collision with obstacles is reduced to the problem of determining the compatibility of systems of linear inequalities. The authors developed an algorithm for solving the problem based on dynamic programming method.